Monitoramento de recursos de transferências voluntárias na esfera municipal - Ignarra, Renata (2014)
This work aims to propose a monitoring tool for voluntary transfers, understood as funds transferred by the Union to the States, Federal District and Municipalities due to the conclusion of conventions, agreements, arrangements or other similar instruments whose purpose is to carry out works and common services and coincident to the three spheres of government interest. Initially are presented the concepts involving the subject grounded in literature survey are realized. Then present the qualitative research study conducted in 78 municipalities of the State of Rio de Janeiro in the period 2009-2013. The research identified that municipalities have difficulty in: i) systematize the information pertaining to the covenants and, ii) monitor its implementation. And finally, is propose a monitoring tool covenants given the importance of these resources for the development of municipalities.